Human-based systems: Mechanistic NASH modelling just around the corner?. (August 2018) - Boeckmans, Joost; Natale, Alessandra; Buyl, Karolien; Rogiers, Vera; De Kock, Joery; Vanhaecke, Tamara; Rodrigues, Robim M.
Graphical abstract: Abstract: Non-alcoholic steatohepatitis (NASH) is a chronic liver disease characterized by excessive triglyceride accumulation in the liver accompanied by inflammation, cell stress and apoptosis. It is the tipping point to the life-threatening stages of non-alcoholic fatty liver disease (NAFLD). Despite the high prevalence of NASH, up to five percent of the global population, there are currently no approved drugs to treat this disease. Animal models, mostly based on specific diets and genetic modifications, are often employed in anti-NASH drug development. However, due to interspecies differences and artificial pathogenic conditions, they do not represent the human situation accurately and are inadequate for testing the efficacy and safety of potential new drugs. Human-based in vitro models provide a more legitimate representation of the human NASH pathophysiology and can be used to investigate the dysregulation of cellular functions associated with the disease. Also in silico methodologies and pathway-based approaches using human datasets, may contribute to a more accurate representation of NASH, thereby facilitating the quest for new anti-NASH drugs. In this review, we describe the molecular components of NASH and how human-based tools can contribute to unraveling the pathogenesis of this disease and be used in anti-NASH drug development. We also propose a roadmap for the development and application of human-based approaches for future investigation of NASH.